Distribution of leptospirosis patients in Sri Lanka: a retrospective study - Karunathilaka, Nimantha; Jayasekara, Kithsiri; Chathurangani, Ishara; Thudugala, Ranga; Silva, Athige Rajith; Ratnasooriya, Wanigasekara Daya (International Journal Of Community Medicine And Public Health, 2017)
Background: Leptospirosis [LP] is zoonotic diseases and one of the main communicable diseases in Sri Lanka [SL]. SL is a tropical country in the Indian Ocean with favorable environmental and geographical conditions for dispersion of the LP infection. The aim of the study was to determine the pattern of distribution with possible environmental conditions/factors contributing to the LP in SL. Methods: The study was carried out as retrospective study from 2009-14 throughout the all 25 administrative districts in SL. Results: The multiple regression was performed to investigate any associations between the prevalence of LP and independent variable parameters namely, annual rainfall, average humidity, area of paddy lands and annual flood data. The results revealed that factors affecting prevalence of the LP in Sri Lanka can’t be investigated in toto. Seasonal analysis is needed in the wet and dry zones corresponding to the main Yala and Maha agricultural seasons. Annual rainfall is mainly associated with the prevalence of LP in the wet zone while agricultural environment associated with the prevalence of LP in the dry zone (p<0.05). Furthermore, geographical distribution, high annual water discharge and low precipitation of the river water provides favorable environment for dispersion of LP in the wet zone whilst large reservoirs with highly functioning cascades correlated in the dry zone in SL. Conclusions: It is concluded that pattern of distribution with possible environmental conditions/factors contributing to the LP in SL is vary in the wet and dry zones.